Genetic variability estimated among caroá populations through RAPD markers - Silveira, Daniela Garcia; Amorim, Edson Perito; Jesus, Onildo Nunes de; Souza, Fernanda Vidigal Duarte; Pestana, Kátia Nogueira; Santos, Vânia Jesus dos; Santana, José Raniere Ferreira de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to quantify the genetic variability within and among populations of caroá (Neoglaziovia variegata) using (RAPD) markers. One hundred eighty caroá genotypes from Guanambi, Juazeiro and Valente counties in the state of Bahia, Brazil, were analyzed. A high polymorphism was observed among the caroá populations. The genetic dissimilarities among all genotypes ranged from 0.08 to 0.95 with an average of 0.44. The molecular variance showed that 56% of the total variation was explained by the differences among individuals within locations. The differences among counties explained 17% of the total variation, while the differences among places within counties explained 26% of the variation.